Count on beat, Sing-apore : a history of sing Singapore and the national songs - Tan, Lynelle Wye Qi (2018)
The history of National songs and the Sing Singapore campaign has not been widely written upon and the sources used to make the arguments in current literature are often speculation of government intentions or what the government chose to say to the public; mediums such as newspapers, speeches and participant interviews. What this paper aims to do differently is to provide a more solid constitutional point of view with two interviews with government individuals that worked on these songs and campaign. This paper studies the national songs and Sing Singapore campaign from 1984 onwards up till 2002. Hence, this paper argues that National songs and the Sing Singapore campaign were used to perpetuate the government’s communitarianism ideology for the purposes of nation building, in terms of defence, and safeguarding the PAP’s political dominance. This argument challenges the current literature that the arts were only used by the government for economic gains and nation building in the 1990s onwards. Overall, this paper hopes to shed light on a different narrative surrounding arts and culture, politics, military defence, national songs and the Sing Singapore campaign.